Radiofrequency Ablation for Trigeminal Neuralgia Patient: A Case Report - Usman; Nur Surya Wirawan (Journal of Anesthesiology and Clinical Research, 2022)
Introduction: Radiofrequency ablation is the most commonly used percutaneous procedure to treat trigeminal neuralgia. This therapy is less invasive, safe, and provides immediate results and minimal side effects. This study aims to demonstrate the potential of radiofrequency ablation in the management of trigeminal neuralgia pain. Case presentation: A 64-year-old man with recurrent trigeminal neuralgia was treated with radiofrequency ablation at Hasanuddin University Hospital. The patient had previously received radiofrequency ablation at the same site as now, and the patient was pain-free for up to three years. After the procedure, complaints of pain gradually subsided for two months until the patient felt pain-free. Conclusion: Radiofrequency ablation is a minimally invasive alternative treatment for chronic pain that is not controlled by pharmacotherapy, such as trigeminal neuralgia. Good knowledge of anatomy and imaging techniques is required for successful therapy. In this patient, the radiofrequency ablation procedure was quite successful, characterized by complaints of pain which gradually subsided in two months until the patient felt pain-free.